Promosi Dan Edukasi Pendidikan Tinggi Melalui Kegiatan Expo Campus Di MAN 01 Batang - Choirunnisa, Choirunnisa; Setiawan, Hendy; Irawan, Rizki Rahmanda; Sutinnarto, Sutinnarto; Erison, Yendra (Hippocampus: Jurnal Pengabdian Kepada Masyarakat, 2024)
The quality of human resources has an important role in encouraging development progress. Regions that have advanced development are usually reflected in one indicator of human development. Therefore, each region continues to compete to increase its HDI index in order to show the level of success of its regional development. The purpose of this article is to discuss the promotion and education of higher education through expo campus activities at MAN 01 Batang. This activity was motivated by the lack of HDI in Batang Regency. The interest of the people of Batang Regency in continuing higher education is still low. This can be seen from BPS statistical data that the HDI in Batang Regency in the 2020-2022 period is still 69-nan. This service method uses an educational promotion approach with a queuing system from class to class. The service team uses brochures, lectures, and also uses a projector screen in activities. To oversee the progress of the event, each student carries a control card so they are required to attend this event until the end. The results show that this activity is able to increase students' interest in continuing to higher education. At first they did not think about continuing to college after they finished school. However, after this activity they were motivated to continue their studies. In fact, they are optimistic that by attending college they will indirectly contribute to increasing the HDI in Batang Regency which is still low).